ASYMMETRICAL CONFLICT AND HUMAN SECURITY: REFLECTIONS FROM KENYA (The Strategic Review for Southern Africa, 2020)
This paper focuses on contemporary challenges to the human security framework through an examination of asymmetrical conflict generated by extremist insurgents, specifically Al Shabaab in Kenya. The political and security dynamics generated by extremist groups often find reinforcement in local contestations over power and territory, resulting in an interaction between local and 'external'. It is the product of these interactions in the form of opportunities, resultant discourses, responses and what they offer to an expansion of normative ideas about human security and conflict that this paper focuses on. Using Kenya as a case study, this paper explores the interface between the growth of Al Shabaab, securitisation of governance and political elite consensus on the policy relationship between human security versus a state security model. This paper pursues the argument that the rise in the intensity and nature of Al Shabaab attacks in Kenya has influenced the interpretation of the country's security  threats and the application of strategies. Rather than aiding the application of human security as central to national security, it has rolled back previous gains.
Keywords: contemporary challenges; human security; asymmetrical conflict; extremist insurgents; Al Shabaab; Kenya; security; power and territory; conflict; securitisation; governance; political elite; consensus; policy; human security versus a state security; security threats; national security